6 - Decentralisation in Uganda: Prospects for Improved Service Delivery - Muriisa, Roberts Kabeba (Africa Development, 2021)
Since the 1980s, many Sub-Saharan African countries have been undergoing structural reforms with a view to promoting efficient service delivery. Decentrali- sation, defined as the transfer of authority from central to local governments to perform certain duties, is seen as one of the public sector reform strategies to increase service delivery. Decentralisation in Uganda began in 1986 with the coming into power of the National Resistance Movement, which aimed at pro- moting democracy and enhancing local participation. In Uganda, political de- centralisation developed along with financial decentralisation. The goal of po- litical decentralisation was to promote people’s participation in the democratic process of Uganda. This took the form of Administrative Units – Resistance Councils (RC)1 running from the village to district levels. Financial decentralisa- tion, on the other hand, attempted to assign responsibilities and taxes between the centre and local governments, to enable the transfer of grants and other resources to different parts of the country, and to improve service delivery. This paper will review different government, public and academic documents as well as findings of other researches such as UN reports about decentralisation and service delivery in Uganda. Based on these sources the paper will answer the following questions: to what extent does decentralisation increase service de- livery? To what extent does decentralisation increase efficiency, participation, accountability and effectiveness? What are the challenges of implementing de- centralisation in Uganda?